Edukasi Interaksi Sosial Mahasiswa Baru Melalui Kemah Dakwah Dan Bakti Mahasiswa (KDBM) Di STAI Sangatta Kutai Timur - Satriah Satriah; Anggra Prima (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
This service aims to strengthen understanding of the importance of social interaction through the Da'wah and Student Service Camp in order to become an entry point in forging spirituality, morality and social responsibility as agents of change and agents of social control in the future. The method used in this research is descriptive analytical method. The technique used in this activity is service learning by carrying out community service through teaching in order to increase the social interaction experience of new students within the Sangatta East Kutai Islamic College with the direction of the supervisor. The results of this research show that social interaction education for new STAI Sangatta students is formulated through the Student Da'wah and Community Service program which includes various activities directly and indirectly with the community.